Implementasi Desain UI/UX Pada Aplikasi Pembelajaran UMKM Dengan Media Video Berbasis Website Pada Siger Innovation Hub: Indonesia - Muhammad Farhan, Farhan; Subyantoro, Eko; Saputra, Kurniawan (Program Studi Teknologi Rekayasa Internet, Politeknik Negeri Lampung, 2024)
Micro, Small and Medium Enterprises (MSMEs) have an important role in a country's economy but often face challenges, especially the lack of access to information and training. Siger Innovation Hub as a business incubator institution offers an incubation class program to support MSMEs with the best government and mentor collaboration. The reality is that technical and time limitations often hinder participant participation and reduce interactivity in learning sessions. Based on the problems described, a solution was found, namely providing an incubation class website platform with a focus on UI/UX design. The method used in this design uses the Double Diamond method. Double Diamond begins with the discovery, definition, delivery, and development stages. UI/UX design for MSME learning applications with website-based video media on the Siger Innovation Hub will be able to make it easy for MSME participants to be able to study flexibly and get a website display that is easy to use, easy to understand and attractive to users.